Determining geographical variations in Ascaris suum isolated from different regions in northwest China through sequences of three mitochondrial genes. (4th May 2017) - Zou, Yong; Wu, Fei; Guo, Ya-Xu; Wang, Hui-Bao; Fang, Yan-Qin; Kang, Ming; Lin, Qing
Abstract: The sequence diversities in three mitochondrial DNA (mtDNA) regions, namely portions of NADH dehydrogenase subunit 1 (p nad1 ), cytochrome c oxidase subunit 1 (p cox 1), and NADH dehydrogenase subunit 4 (p nad 4), were investigated in all Ascaris suum samples isolated from four regions in northwestern China. Those genes were amplified by PCR method and the lengths of p nad 1, p cox 1, and p nad 4 were 419 bp, 711 bp, and 723 bp, respectively. The intraspecific sequence variations within A. suum samples were 0–2.9% for p nad 1, 0–2.1% for p cox 1, and 0–3.1% for p nad 4. Phylogenetic analysis combined with three sequences of mtDNA fragments showed that all A. suum samples were monophyletic groups, but samples from the same geographical origin did not always cluster together. The results suggested that the three mtDNA fragments could not be used as molecular markers to identify the A. suum isolates from four regions, and have important implications for studying molecular epidemiology and population genetics of A. suum .